(untitled) (Journal of Parents and Teachers, 2026)
A school in England had an excellent idea to improve its students’ French language learning. They built a classroom that realistically reproduces a typical French street so that students can practise the language immersed in everyday scenes, rather than just reciting verbs in class. On another note, what is your relationship with books like? The French youth magazine Phosphore divides readers into four categories: bibliophobes, bibliophages, bibliophores and bibliophiles. And, take note, Italian museums are considering measures to regulate the mass entry of students who are not accompanied by their teachers and divided into small groups. Find out more here.